O rendimento escolar dos jovens no contexto do ensino médio nas escolas do município de Soure – Ilha de Marajó - Pará - NASCIMENTO, Luana Santos (2024)
The work in question discusses the theme of school performance in high school. To this end, the study aims to analyze the school performance of young people from the perspective of high school in schools in the municipality of Soure, Ilha de Marajó – PA. Thus, for the development of this study, qualitative and quantitative research is used (MINAYO, 2009; ZANELLA, 2009), from which it was possible to carry out a bibliographic and documentary survey (MARCONI and LAKATOS, 2007), resorting to studies that dialogue more broadly on the proposed theme, using content analysis as a technique (BARDIN, 1977). The locus of the research extended to the high schools of the city of Soure, obtaining accurate information on the digital platform of the National Institute of Educational Studies and Research Anísio Teixeira (INEP), whose focus was on school performance based on the flow of data from the indicators pass, fail, dropout and age-grade distortion, in addition to transiting with data from the geographic units of Marajó, Pará and Brazil. In this context, understanding that there is a lack of studies in the city aimed at young people working in high school, it was thought to deepen the investigations, contributing not only to future academic works, but also to the development of new studies, for the community by proposing to research the educational performance of young people in public medium institutions in the locality of sourense. The theoretical foundation is based on the arguments of renowned authors and official documents within the proposal worked on in this study (ALVES and ARAÚJO, 2017; FRIGOTTO, 2001; KRAWCZYK, 2009; FAPESPA, 2018; GOLDEN, 2007; GADOTTI, 2013; BRAZIL, 1988 and 1996) and among others. In view of the results obtained regarding academic performance in secondary education, the data on the indicators of failure, abandonment and age-grade distortion present high numbers, whether in schools in the municipality or in the geographical divisions of Marajó, Pará and Brazil, which is possible to mention the demand for public policies, especially when it comes to the last stage of basic education in the municipality of Soure, and even in the geographical divisions of Marajó, Pará and Brazil.